Estimating vector-borne viral infections in the urban setting of the 2020 Tokyo Olympics, Japan, using mathematical modeling - Furuya, H. (Tokai Journal of Experimental and Clinical Medicine, 2018)
The first domestic outbreak of dengue fever in Japan since 1945 was reported in Tokyo in 2014. Meanwhile, daily mean summer temperatures are expected to continue to rise world-wide. Such conditions are expected to increase the risk of an arbovirus outbreak at the 2020 Tokyo Olympic Games. To address this possibility, the present study compared estimates of the risk of infection by dengue, chikungunya, and Zika viruses in urban areas. To compare the risk of infection by arboviruses transmitted by Ae. albopictus mosquitoes, the reproduction number for each of three arboviruses was estimated under the environmental conditions associated with the 2014 dengue outbreak in Tokyo, and additionally under conditions assuming a daily mean temperature elevation of 2° C. For dengue, chikungunya, and Zika, the estimated distributions of R0 were independently fitted to gamma distributions yielding median R0 values of 1.00, 0.46, and 0.36, respectively. If the daily mean temperature were to rise from 28° C to 30° C, our model predicts increases of the median R0 of 18% for dengue, 4.3% for chikungunya, and 11.1% for Zika. Strengthening of the public health responsivity for these emerging arboviral diseases will be needed in preparation for the 2020 Olympic Games in Tokyo.